RANCANG BANGUN SISTEM PEMBELIAN BAHAN BAKU PADA CV MEDIA KARYA - Sri Rodziyah; Sarana -; Nikmatuniayah - (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2019)
The purpose of this study is to create a design system for purchasing raw material information at CV Media Karya to facilitate the management of purchases. This study uses primary data and secondary data in the form of quantitative data and qualitative data. Data collection techniques used are observation, interviews and literature. This raw material purchasing system is made using Microsoft Visual Basic 6.0 while database storage uses Microsoft Access and Crystal Report 8.5 to generate reports. The development method used is SDLC (System Development Life Cycle). This raw material purchasing system application can overcome the problems found in CV Media's work on the raw material purchasing system and can provide a reminder of the stock in the use of raw materials. Input data in this application are supplier data, material type data, initial inventory balance, purchase and use of raw materials. This application generates purchase reports, supplier data reports, debt data reports, raw material reports and inventory mutation reports.